Inquiry-Based Supplementary Learning Materials in Living Things and Their Environment - Arevalo, Lester Gene; Reyes, Edilbert (Journal of Interdisciplinary Perspectives, 2025)
Despite the focus on science mastery in the K to 12 curricula, there is still a lack of contextually developed and validated supplementary learning materials specifically designed to improve Key Stage 2 pupils' understanding of science competencies. This study aimed to address this gap by developing inquiry-based supplementary learning materials focused on the least mastered competencies in the topic "Living Things and Their Environment." It sought to answer the following questions: (1) What are the least mastered competencies to be included in developing the materials? (2) What inquiry-based materials can be developed from these competencies? (3) How valid are the content, format, presentation, organization, and accuracy of the developed materials? (4) What is the mastery level of pupils before and after using the materials? (5) Is there a significant difference in the mean pretest and posttest scores? The study used a research and development method with a one-group pretest-posttest quasi-experimental design. Fifteen validators assessed the quality of the materials, and 156 Key Stage 2 pupils participated. The mastery level was measured using the Mean Percentage Score (MPS), and an ANOVA was used to test the significance of the differences in scores. Findings showed an increase in the mastery level from Average Mastery to Moving Towards Mastery. ANOVA results revealed no significant difference in Grade 4 scores but showed a significant difference for Grades 5 and 6. The developed materials effectively improved science mastery, especially at higher grade levels. Based on these findings, the researcher recommends publishing the developed inquiry-based supplementary learning materials in the Learning Resources Management and Development System (LRMDS) portal of the Department of Education (DepEd) for use by both teachers and students as an instructional tool in elementary science education.